Revisiting the mechanisms linking blood glucose to cognitive impairment: new evidence for the potential important role of klotho - Liu, Xiangliang; Li, Yuguang; Chen, Xinqiao; Yin, Hongmei; Li, Fangqi; Chen, Naifei; Cui, Jiuwei; Li, Wei (Frontiers in Endocrinology, 2024)
Background The association between blood glucose and cognition is controversial. Klotho is an anti-aging protein with neural protective effects. This study aimed to use a population-based study to disentangle the relationship between blood glucose levels and cognitive function in older adults, and to explore the role of klotho in it. Methods A total of 1445 eligible participants from National Health and Nutrition Examination Survey (NHANES) 2011-2014 were included in our study. Cognitive function was assessed by Digit Symbol Substitution Test (DSST) and categorized into four quartiles (Q1-Q4). General characteristics and laboratory test results including serum klotho concentration and blood glucose levels were collected. Associations of cognitive function and klotho levels with blood glucose concentrations were explored through multivariate linear regression models. Mediation models were constructed to figure out the mediating role of klotho. Results All three multivariate linear regression models showed a negative correlation between blood glucose and cognitive function. (Model 1, β=-0.149, 95%CI: -0.202,-0.096, p=0.001; Model 2, β=-0.116, 95%CI: -0.167,-0.065, p=0.001; Model 3, β=-0.007, 95%CI: -0.118,-0.023, p=0.003). Mediation analysis showed that klotho mediated the statistical association between blood glucose level and cognitive function with proportions (%) of 12.5. Conclusion Higher blood glucose levels are associated with poorer cognitive performance in non-diabetic older adults, partially mediated through lower klotho levels.